Cross-reactivity and sensitization profiles of cockroach and moth allergens provide new insights in cockroach-allergic patients - Jiale Zhang, Doctor of Medicine (M.D.); Aoli Li, Master of Medicine; Li Liu, Master of Medicine; Bo Chang, Master of Medicine; Wenting Luo, Doctor of Medicine (M.D.); Baoqing Sun, Master of Medicine (World Allergy Organization Journal)
Background: Inhalant insect allergens are widely implicated as common triggers of respiratory allergies, but little is known about cross-reactivity between cockroaches and other insect allergens. This study mainly investigates sensitization profiles and cross-reactivity between cockroach allergens and moth allergens to provide insights into the clinical management of cockroach-allergic patients. Methods: A total of 386 suspected cockroach-sensitized patients were enrolled. Sensitization rates were determined using IgE testing for common airborne allergens. Cross-reactivity was evaluated using IgE inhibition assays, immunoblotting, and basophil activation tests. Age-related sensitization patterns were analyzed to assess variability in immune response across different demographics. Results: A high frequency of silk moth was observed in cockroach-sensitized patients, with sensitization rates to German cockroach and silk moth allergens at 81.09% and 81.61%, respectively, and a high co-sensitization rate (54.66%). Age analysis revealed similar peak sensitization of German cockroach and silk moth in school-age children and young adults, with a lower prevalence in the elderly. Additionally, cockroach crude extract can inhibit the IgE-binding of cockroach-sensitized patients' sera and silk moth crude extract, while various moths can activate basophils as well. Conclusions: This study highlights the similar age-related sensitization patterns between German cockroach and silk moth, differing from those observed with house dust mites. Besides, cross-reactivity between different cockroach and moth allergens was confirmed through significant IgE inhibition, multiple sequences alignment of shared epitopes and basophil activation tests. These findings highlight the need to consider cross-reactivity between cockroach and moth allergens in clinical evaluations.